Implementation Implementation of Positive Discipline in Learning Management at State Elementary School 4 Kaliaman, Kembang District, Jepara Regency (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze the planning, implementation, and evaluation of positive discipline implementation in learning management at SD Negeri 4 Kaliaman, Kembang District, Jepara Regency. A positive discipline approach is important to be implemented to foster self-control, responsibility, and awareness of students without using physical or psychological punishment, while creating a conducive learning environment. Method: This study aims to analyze the planning, implementation, and evaluation of positive discipline implementation in learning management at SD Negeri 4 Kaliaman, Kembang District, Jepara Regency. A positive discipline approach is important to be implemented to foster self-control, responsibility, and awareness of students without using physical or psychological punishment, while creating a conducive learning environment. Results: The findings show that positive discipline was implemented systematically through structured planning, consistent implementation, and continuous evaluation. The program involved regular class meetings, teacher training, positive reinforcement, and collaborative participation among school members. The implementation of positive discipline improved students’ character competencies, particularly responsibility, self-discipline, cooperation, and respectful behavior. In addition, the program reduced disciplinary violations and created a more conducive and supportive learning environment. Novelty: The novelty of this research lies in the comprehensive analysis of the implementation of positive discipline in learning management in elementary schools that integrates the planning, implementation, and evaluation processes and is supported by the collaborative involvement of all school members.